Impact of Multidirectional Transverse Calf Muscle Loading on Calf Muscle Force in Young Adults - Siebert, Tobias; Eb, Manuel; Ryan, David S.; Wakeling, James M.; Stutzig, Norman (Frontiers in Physiology, 2018)
It has been demonstrated that unidirectional transversal muscle loading induced by a plunger influences muscle shape and reduces muscle force. The interaction between muscle and transversal forces may depend on specific neuromuscular properties that change during a lifetime. Compression garments, applying forces from all directions in the transverse plane, are widely used in sports for example to improve performance. Differences in the loading direction (unidirectional vs. multidirectional) may have an impact on force generating capacity of muscle and, thus, on muscle performance. The aim of this study was to examine the effect of multidirectional transversal loads, using a sling looped around the calf, on the isometric force during plantarflexions. Young male adults (25.7 ± 1.5 years, n = 15) were placed in a prone position in a calf press apparatus. The posterior tibial nerve was stimulated to obtain the maximal double-twitch force of the calf muscles with (59.4 N and 108.4 N) and without multidirectional transverse load. Compared to the unloaded condition, the rate of force development was reduced by 5.0±8.1 % (p=0.048) and 6.9±10.7 % (p=0.008) for the 59.4 N and the 108.4 N load, respectively. No significant reduction (3.2±4.8 %, p=0.141) in maximum muscle force (Fm) was found for the lower load (59.4 N), but application of the higher load (108.4 N) resulted in a significant reduction of Fm by 4.8±7.0 % (p=0.008). Mean pressures induced in this study (14.3 mm Hg and 26.3 mm Hg corresponding to the 59.4 N and 108.4 N loads, respectively) are within the pressure range reported for compression garments. Taking the results of the present study into account, a reduction in maximum muscle force would be expected for compression garments with pressures ≥ 26.3 mm Hg. However, it should be noted that the loading condition (sling vs. compression garment) differs and that compression garments may influence other mechanisms contributing to force generation. For example, wearing compression garments during exercise may enhance performance by enhanced proprioception and reduced muscle oscillation. Thus, superposition of several effects should be considered when analyzing the impact of compression garments on more complex sport performance.